Principles of Gene Manipulation and Genomics - Sandy B. Primrose (Blackwell Publications, 2011)
There Has Been Rapid Progress In Recombinant Dna Technology Over The Last Few Years, Particularly In The Area Of Large-scale Biology (genomics And Related Disciplines). The Increasing Integration Between Gene Manipulation And Genomics Is Embraced In This Book, Principles Of Gene Manipulation And Genomics, Which Brings Together For The First Time The Subjects Covered By The Best-selling Books Principles Of Gene Manipulation And Principles Of Genome Analysis And Genomics. This Important New Text Has Been Comprehensively Revised, Updated, And Rewritten To Encompass Within One Volume, Basic And Advanced Gene-manipulation Techniques, Genome Analysis, Genomics, Transcriptomics, Proteomics, And Metabolomics, As Well As The Applications Of These Fascinating Technologies. Principles Of Gene Manipulation And Genomics Is An Accessible And Up-to-date Guide To This Exciting Field, And Is The Essential Reference For Upper-level Undergraduate And Graduate Students Of Genetics, Genomics, Molecular Biology, And Recombinant Dna Technology.